Analisis Pendapatan Usahatani Padi Sawah Di Desa Biontong Kecamatan Bolangitang Timur Kabupaten Bolaang Mongondow Utara - Kantohe, Cheriyl; Sondakh, Mex Frans Lodwyk; Benu, Noortje Marsellanie (Sam Ratulangi University, 2024)
The purpose of this study was to determine how much income is obtained by wet-rice farmers in Biontong 1 Village, East Bolangitang District, North Bolaang Mongondow Regency. The analysis method used is profit analysis which calculates the difference between revenue and total costs incurred. The results of this study reveal that farming activities generate significant profits and are feasible to cultivate. The relatively high amount of income per hectare gives a positive indication of the profitability of the farm. Therefore, it can be concluded that paddy rice farming in Biontong Village, Bolangitang Timur Sub-district has good potential in providing economic benefits to farmers, and the sustainability of this activity can be considered.